Induksi Mutasi pada Stek Pucuk Anyelir (Dianthus caryophyllus Linn.) melalui Iradiasi Sinar Gamma - Syarifah Iis Aisyah; Hajrial Aswidinnoor; Asep Saefuddin; Budi Marwoto; Sarsidi Sastrosumarjo (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2009)
It has been a common knowledge that LD50 is commonly used in estimating optimal doses of gamma irradiation in a breeding program. This research was aimed at observing radiosensitivity of five carnation's genotypes to gamma irradiation, to find the LD50 of carnation's cuttings, and to obtain solid mutants from five numbers of Carnation.  For cuttings, carnation genotype number 10.8 was the most insensitive to gamma rays, whereas number 24.15 was the most sensitive one.  LD50 of carnation's cuttings were obtained around 49 -72 gray. There were 19 mutants produced from this treatment. The desired mutans were mostly produced from the treated 24.1 genotype whereas the character mutans were mostly observed in MV2 generation. Irradiation treatment on genotype 24.1 produced most stabile mutans while the less was in genotype 24.14.  The produced mutants were qualitatively different in colour and petal shape, and stabile till third generation.   Key words: LD50, gamma irradiation, induced mutation, carnation.